2021
DOI: 10.1002/aelm.202100687
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Insulator‐to‐Metal Transition of VO2/TiO2 Epitaxial Bilayer Films Grown on M‐plane Sapphire Substrates

Abstract: Since the optoelectronic properties of VO2 are modulated around the critical temperature (Tc) of insulator‐to‐metal transition, VO2 is a promising candidate material for smart window. However, the Tc of bulk VO2 is rather high 341 K (68 °C) and therefore, needs to be decreased down to near temperature for practical applications. Although Tc can be reduced to room temperature if rutile TiO2 crystal is used as the substrate, it is not technologically viable for large‐scale applications because of the size limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Because the very small lattice mismatch (∼0.9%) between (001) R–VO 2 and (001) R–TiO 2 stabilizes the R–VO 2 lattice at room temperature using a (001) TiO 2 substrate significantly reduces the T c of an epitaxial VO 2 film . Additionally, a similar effect has been experimentally demonstrated using a TiO 2 buffer layer grown on another substrate. ,, …”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Because the very small lattice mismatch (∼0.9%) between (001) R–VO 2 and (001) R–TiO 2 stabilizes the R–VO 2 lattice at room temperature using a (001) TiO 2 substrate significantly reduces the T c of an epitaxial VO 2 film . Additionally, a similar effect has been experimentally demonstrated using a TiO 2 buffer layer grown on another substrate. ,, …”
Section: Introductionmentioning
confidence: 76%
“…However, the transition temperature ( T c ) of bulk VO 2 (∼68 °C) is still too high for use in practical applications. In the past few decades, many studies have investigated strategies to reduce T c of VO 2 . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of MIT shift and mechanical stresses in VO 2 /TiO 2 films was reported by several authors. However, a related MIT is typically shifted to a lower temperature [ 38 , 39 ]. Therefore, YX-128° cut LiNbO 3 substrate likely results in mechanically induced MIT shift to a higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…According to the differential curve in the insert, it can be observed that the phase transition temperature in the heating process is 67.7 °C, and that in the cooling process is 62.3 °C, which is very consistent with the previous report. [40,41] Figure 1d shows the SEM cross-section of the film, where a distinct difference between the VO 2 film and the alumina substrate can be observed. The Surface topography of the VO 2 sample was also examined by SEM and AFM as shown in Figure 1e and Figure S1, Supporting Information.…”
Section: Characterizations Of the Epitaxial Vo 2 Filmmentioning
confidence: 99%